Beyond digital international tourism communication network for tourism quality improvement - Nirwana, Maya Diah; Maksum, Ali; Avicenna, Fitria; Fidarijanthi, Ratu Aulia (Faculty of Communication Sciences Universitas Padjadjaran, 2024)
Collaboration is essential for any tourism location to be successful in solving difficulties. The study aims to explore the motivations behind the collaboration of Malang Raya (Greater Malang), Indonesia. We focus on the prerequisites organizations must meet to participate in collaborative international tourism initiatives. We applied the qualitative technique. There are 30 informants from public relations, governments, scholars, media, international tourists, travel agents, communities, and tourism associations. We conducted semi-structured interviews and observations. The results demonstrate that the digital network of international tourism communication collaboration in Malang Raya is not optimal yet. The efforts made by the Destination Management Organization (DMO) in Malang Raya in the future will become a ‘diamond’ for improving the quality of tourism. International tourism will be brilliant, valuable, and of good quality. The international tourism communication collaboration digital network implemented: a) the digital collaboration between tourism departments at some universities in Malang Raya with some hotel companies and the Association of the Indonesian Tours and Travel Agencies; b) the digitalization of small and medium enterprises collaboration in Malang Raya, Indonesia such Batu Local Guide; c) online taxi which operated in Malang Raya destinations namely Grab and Uber to facilitate international tourists reach the destinations; d) for improving digital tourism communication network, Malang Raya has Malang Tourism Information Centre; e) Malang Raya destinations collaborated with smartphone sim card providers in tourism information services; f) Malang Raya has ngalam.co, and gumebyar.malangkab.go.id to integrate destination information and accommodations.